2016
DOI: 10.1002/wat2.1152
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and ‘fracking’: a review of (the limited) moral thought on shale gas development

Abstract: Whilst claims about the ethicality of shale gas development via hydraulic fracturing or 'fracking', are commonplace in everyday discourse, little scholarly attention has been afforded explicitly to this aspect of unconventional fossil fuel extraction. The limited research that speaks to ethical considerations largely describes ethical concerns associated with development-extremely few claims in research literature make an ethical case for development. The most common ethical concerns cited in research stem fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…A major focus in our sample was the degree to which wealth, social costs, and changes in quality of life are distributed (un)evenly or (in)equitably amongst a range of actors exposed to shale operations (see Ref for a recent review). Most of these authors provided evidence for uneven distribution of benefits and/or harms associated with development, or for people's concerns about such uneven distribution.…”
Section: Perceptions Of Shale Operations In the Us And Canadamentioning
confidence: 99%
“…A major focus in our sample was the degree to which wealth, social costs, and changes in quality of life are distributed (un)evenly or (in)equitably amongst a range of actors exposed to shale operations (see Ref for a recent review). Most of these authors provided evidence for uneven distribution of benefits and/or harms associated with development, or for people's concerns about such uneven distribution.…”
Section: Perceptions Of Shale Operations In the Us And Canadamentioning
confidence: 99%
“…Indeed, research has shown concerns about procedural justice to be amongst the leading normative claims shaping perceptions of shale gas development (Cotton 2013, Evensen 2015, 2016a, Whitton et al 2017.…”
Section: Implications For Communicationmentioning
confidence: 99%
“…All forms of energy development, even wind and solar, have negative environmental consequences (e.g., during production and installation) (Duggan-Haas et al, 2013). Avoiding environmental damage is not possible, but having a principled and non-arbitrary threshold for the damage one is willing to accept is possible (Evensen, 2015); a conversation about justice considerations is relevant here (Cotton, 2016;Evensen, 2016;Sovacool and Dworkin, 2015).…”
Section: The Democratsmentioning
confidence: 99%